Task integration and anticipation in complex, continuous motor tasks - Patrick Beißel; Stefan Künzell (Frontiers in Psychology)
Multitasking and sequential motor learning research has advanced greatly in recent years, yet commonly accepted insights are largely based on simple, distinct tasks which cannot accurately reflect the variety of more complex and continuous tasks we encounter in everyday life. This study therefore aims to reassess the influence of task integration on motor sequence learning in complex, continuous tasks through the use of a virtual reality environment and an adapted SRT dual task suited for continuous movements. In our experiment, participants performed a complex, bimanual motor sequence task with varying degrees of suitability for task integration. We could successfully show that task integration has beneficial effects on complex task acquisition if covariations between tasks are consistent and detrimental effects if covariations are too inconsitent or missing. Minor inconsistencies within a repeated sequence can however be mitigated. These results highlight the distinct influence of task integration on complex, continuous motor learning, yet emphasize the need for further research beyond distinct, simple tasks.